Christian Ethics and Ecologies of Violence - Kreider, Luke Beck (Religions, 2019)
This essay introduces "ecologies of violence" as a problem for Christian ethics. Understanding the links between violence and the natural environment will be critical to the pursuit of justice, peace, and sustainability in the twenty-first century. Yet these links often evade political action and escape moral attention because they do not fit comfortably within any of the fields requisite to address them. In most cases, the available resources for confronting these issues "environmental issues" and "peace and conflict issues" exist in separate toolkits, and no single discourse has developed resources to address their progressively merging spheres of concern. The essay outlines four types of ecological violence, examines recent work in Christian ethics relevant to them, and then argues for a dialogical method of ethics to confront them. Doing Christian ethics at the intersections of violence and environmental issues will require careful attention to environmental ethics as well as to the ethics of violence. More than that, it will require judicious efforts to navigate between them within case-based and place-based ethical analyses. Ecologies of violence invite Christian ethics to develop possibilities of ethical discernment and reparative action that do justice to the deep entanglement of ecological and sociopolitical systems.